Theoretical electronic structure with dipole moment and rovibrational calculation of the low-lying electronic states of the HgF molecule. (November 2017) - Elmoussaoui, Soumaya; Chmaisani, Wael; Korek, Mahmoud
Highlights: For HgF molecule we investigated. Potential curves with dipole moment of 18 states with the constants Te, R e, ω e, De . Rovibrational parameters Ev, Bv, Dv and Rmin and Rmax . Einstein constants and Franck–Condon factor. Abstract: With the lack of evitable data about the electronic structure of the low-lying states of the HgF molecule unlike its counter parts of mercury monohalides, spectroscopic study of eighteen low-lying doublet and quartet electronic states in the representation 2s+1 Λ (+) of this molecule is conducted. Adiabatic potential energy curves of those states are investigated using the complete active space self consistent field (CASSCF) calculation with multi-reference configuration interaction (MRCI) method including single and double excitations with Davidson correction (+ Q ). The spectroscopic constants as Re, ωe, ωe xe, Be, αe, Te and μe are calculated for the bound states. The dissociation energy D 0 0 and the percentage ionic character fionic are also computed. The transition dipole moment μ TDM between some doublet low-lying states is studied and some emission coefficients as the Einstein spontaneous coefficients A 21, the spontaneous radiative lifetime τ spon, and the oscillator strength f 21 are thus determined. A rovibrational study has been done to investigate the vibrational levels of the low-lying bound states and the vibrational constants E v, B v, D v, Rmin and Rmax are reported. The Franck–Condon factors have also been calculated for the most probable transitions between the excited states and the ground state. The comparison between the values of the present work and those short information available in the literature shows good accordance. Graphical abstract: For the molecule HgF the potential energy curves of 18 electronic states in the representation 2Λ (+/-) have been calculated along with the spectroscopic constants, the static and transition dipole moment, the Einstein spontaneous coefficients, the Franck–Condon factor and a revibrational calculation of the investigated electronic states.